Cyclic CO2 storage operation driven entirely by geothermal power - Nan Tai; Xiaolin Bao; Ian Gates (Heliyon)
Decarbonization is a global priority, and CO2 sequestration is one method to achieve this goal. However, large-scale implementation is difficult due to the costs and emissions involved. A promising approach is to combine CO2 sequestration with geothermal energy generation. This study explores a system using six horizontal wells for cyclic CO2 injection and hot water extraction in the Basal Cambrian Sandstone Unit, Canada by using detailed geothermal modelling. The results indicate that the electricity generated from geothermal energy can offset the energy required for CO2 injection, potentially achieving net-zero emission CO2 storage. A shut-in period between injection and production improves CO2 storage but may reduce total power output. The best CO2 storage performance occurred with synchronized injection and production timings across wells, though this resulted in lower power generation. Conversely, staggered injection and production timings enhanced power generation but reduced CO2 storage efficiency. These findings suggest that it is possible to design processes where the geothermal energy produced can cover the operational energy needs of CO2 sequestration, offering a viable path to emission-free carbon storage operations.